Análisis económico de 14 cultivares de garbanzo, sembrados en Barva de Heredia y San Rafael de Alajuela (ING) - Rojas A., Marvin (1993)
In Costa Rica, the chickpea (Cicer arietinum L.) as a crop, is under experimental evaluations. Satisfactory results have been obtained as tp adaptation of several cultivars and yield of dry grains. In addition agronomic information about the management of this crop has been generated.To support the development of this agricultural activity, an economic analysis was done, based on the performance of 14 cultivars, planted during 1990 in Barva de Heredia and San Rafael de Alajuela.The analysis showed that in Barva the cultivars ILC 114, FLIP 86-9C, ILC 482, ILC445, ILC 464 and FLIP 87-5C has good profitability and a net return of each colon invested from 0.27-0.85, also the cost-benefit ratio ranged between 1.27 and 1.85. In San Rafael only four cultivars showed good profitability (ILC 482, FLIP 85-1C, FLIP 85-15C, FLIP 87-7C) with a net return for each invested colon among 0.42 and 1.16; the cost benefit ratio varied from 1.42 to 2.16.